Escherichia coli growing under antimicrobial gallium nitrate stress reveals new processes of tolerance and toxicity - Daniel A. Salazar-Alemán; Raymond J. Turner (Scientific Reports)
Abstract Metals have been used throughout history to manage disease. With the rising incidence of antibiotic-resistant bacterial strains, metal-based antimicrobials (MBAs) have re-emerged as an alternative to combat infections. Gallium nitrate has shown promising efficacy against several pathogens. Although its main toxicity mechanisms have focused on oxidative stress and its “trojan horse” iron mimetic strategy, there are still many knowledge gaps in the full-systems response elicited to counteract its toxic effects, especially in non-acute toxicity models that evaluate longer exposure times. In this study, we explore the transcriptomic response profile of Escherichia coli K12 BW25113 when challenged to grow planktonically for 10 h in the presence of a sublethal inhibitory concentration of gallium nitrate. 581 genes were significantly up-regulated, and 791 down-regulated. Some of the affected biological systems identified in our analysis include iron homeostasis, sulfate metabolism, oxidative and nitrosative stress response, cysteine biosynthesis, anaerobic respiration, toxin-antitoxin interactions, and DNA repair. Altogether, this work provides a valuable snapshot of how E. coli acclimates to this MBA and expands the current knowledge of mechanisms of sensitivity and tolerance. This is a significant step in understanding how bacteria can adjust their physiology to coexist with sublethal concentrations of toxic metals.